Islamic Banking in Indonesia: An Analysis of Regulation, Operations, and Contemporary Issues from the Perspective of Sharia and Economic Transformation - Khaerunnisa Wahid; Supriadi Supriadi; Kamaruddin Kamaruddin (Lembaga Yasin AlSys, 2025)
Islamic banking in Indonesia has undergone significant growth since the establishment of Bank Muamalat in 1991. This study examines the regulatory framework, operational principles, and the challenges and opportunities facing Islamic banking in addressing contemporary financial issues. Utilizing a descriptive-qualitative approach through a literature study, the research identifies Law No. 21 of 2008 and fatwas issued by the National Sharia Council–Indonesian Ulema Council (DSN-MUI) as the primary legal and ethical foundations for Islamic banking operations. Key contract mechanisms such as muḍārabah, mushārakah, and murābaḥah serve as Sharia-compliant alternatives to conventional interest-based systems. Despite this progress, Islamic banking faces several challenges, including low levels of Sharia literacy among the public, limited digital innovation, and intense competition with conventional banks. However, significant opportunities exist through partnerships with Islamic fintech, integration of Islamic social finance instruments (ZISWAF), and the promotion of sustainable finance initiatives aligned with the objectives of maqāṣid al-sharīʿah. The study underscores the need to strengthen regulatory frameworks and embrace technological advancements to build an inclusive, competitive, and future-ready Islamic banking system in Indonesia.